Hooligans: The product of Marginalization and Academic Shortcomings? An Approach from the Subject as Decider (2016)
Through a deductive analysis we got a characterization of the current situation of “hooligans” in Bogota. This is carried out from two foci: social marginality and truncated education as the foundation of membership in these fanatic groups. Based on the results of the main “hooligan” member surveys located in Bogota we found strong relationships between the two foci of causal analysis (social marginality and truncated education) with the possibility of belonging to these groups.